Illness perceptions amongst individuals with dental caries (2018)
Objective: To assess individuals’ perception of dental caries, in order to explain how illness representations might influence their coping with the disease. Methods: Cross-sectional questionnaire study. Participants: 520 consecutive patients (aged ≥18 years) of the General Dentistry Clinic at Universidad Cooperativa de Colombia, Pasto, Colombia who had experienced dental caries. Main Outcome Measures: Illness perception of dental caries was assessed using the Illness Perception Questionnaire Revised (IPQ-R). Results: The most frequent self-reported symptoms associated with dental caries were “toothache” (56.2%), “tooth sensitivity” (53.8%) and “mild to sharp pain when eating or drinking” (51.2%). The dimensions of illness perception were related to socio-economic status (SES). Symptoms of “loose or separating teeth” and “pus in your tooth” were associated with dental caries by low SES participants, while “bleeding while brushing, flossing or eating hard food” and “mild to sharp pain when eating or drinking something sweet, hot or cold” were related more to higher SES. Conclusions: Perceptions of caries were related to socioeconomic status. Interventions to promote health literacy in order to improve the capacity to obtain, process and understand basic oral health information could increase an early detection of caries.